Dependência de jogos eletrônicos em adolescentes na unidadepediátrica de um Hospital Universitário no Distrito Federal - Isadora de Oliveira Cavalcante; Marilúcia Rocha de Almeida Picanço; Alice Gomes Duart; Bruna Dellatorre Diniz; Ian Carvalho Bezerra; Luana Fernandes de Matos; Marina de Freitas Ferreira; Eduardo Freitas da Silva (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: The study aimed to identify the prevalence of addiction and the risk of addiction to electronic games in adolescents monitored at the Pediatric Service of a university hospital in Distrito Federal. METHODS: Cross-sectional observational study carried out with adolescents aged 10 to 19 years, using a questionnaire of 10 multiple-choice questions, which aim to assess dependency in 5 dimensions in relation to "compulsive gaming". Were also evaluated: sociodemographic data (age, sex, education and grade repetition) and game usage parameters (frequency of weekly gaming, daily game time). The questionnaire was applied in 4 months and the statistical analyzes were performed by the SAS 9.4 application. p <0.05 was considered significant. RESULTS: 114 adolescents were interviewed, with a median age of 15 years. The majority (71%) reported using some type of electronic game as a recreation, of which 62.1% were boys. The prevalence of dependence was 3.51% and the risk of dependency was 9.65%, with the dimension "time restriction" being the most frequent with 42.9%. Only schooling showed a significant association with the occurrence of the risk of dependency (RP = 6,16, IC 95%: 1,48; 25,65; p = 0,0125). DISCUSSION: Even with some limitations, the study stands out for being able to demonstrate a prevalence of dependence on electronic games in a convenience sample similar to the one found in the literature, as well as to draw an epidemiological profile of risk factors for the dependence of the interviewed patients.